Marketing Strategy for Early Childhood Education (ECE) Schools in the Digital Age - Hegar Harini; Dessy Putri Wahyuningtyas; Sutrisno Sutrisno; M. Indre Wanof; Abu Muna Almaududi Ausat (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
In the contemporary technological era, the significance of marketing for educational institutions has experienced a significant surge. The effective execution of marketing tactics can aid in the recruitment of prospective students and concurrently elevate the standing of the institution. Marketing initiatives should be carried out prudently and in accordance with the technological progressions that occur. The objective of this study is to furnish insights for early childhood education institutions in formulating efficacious marketing tactics that align with contemporary demands. The primary emphasis of this investigation is on qualitative analysis. Methods for gathering information include paying close attention and taking detailed notes, with subsequent analysis including data reduction, visualisation, and conclusions. The results of this study show that to develop marketing strategies in the digital era, schools need to consider factors such as market characteristics and needs, the use of social media and online platforms, data security, the quality of educators, and the needs of students. Therefore, they should consider the needs and characteristics of the market and develop educational content that is relevant and appealing to prospective students and parents, which implies that by optimising technology and online platforms and considering the needs and characteristics of the market, schools can improve the reputation and quality of education offered and help increase parental and community involvement in promoting education.